Proteggere la libertà di pensiero - Marsili, M. (Nonmollare, 2025)
ENGLISH ABSTRACT In this article, Marco Marsili explores the growing threats to freedom of thought in the digital age, particularly in the context of algorithmic censorship, regulatory overreach, and cognitive warfare. Drawing on recent European legislation such as the Digital Services Act (DSA) and the Artificial Intelligence Act (AI Act), Marsili highlights how automated moderation systems and preemptive content removal practices risk stifling legitimate debate and critical voices. He argues that democratic societies must resist this drift toward invisible censorship by promoting transparency, accessible appeal mechanisms, and digital literacy. The article also examines the role of international cooperation and alternative, open digital spaces in safeguarding cognitive freedom. “Non mollare” ("Don’t give up") becomes both a motto and a civic responsibility: defending thought diversity, algorithmic accountability, and open dialogue as pillars of democracy. ITALIAN ABSTRACT In questo articolo, Marco Marsili analizza le crescenti minacce alla libertà di pensiero nell’era digitale, con particolare attenzione alla censura algoritmica, all’eccesso regolatorio e alla guerra cognitiva. Prendendo in esame recenti normative europee come il Digital Services Act (DSA) e l’Artificial Intelligence Act (AI Act), l’autore evidenzia come i sistemi automatizzati di moderazione e le pratiche di rimozione preventiva dei contenuti rischino di soffocare il dibattito legittimo e le voci critiche. Marsili sostiene che le società democratiche debbano contrastare questa deriva verso una censura invisibile, promuovendo trasparenza, meccanismi di ricorso accessibili e alfabetizzazione digitale. L’articolo esplora inoltre il ruolo della cooperazione internazionale e degli spazi digitali alternativi e open source nella tutela della libertà cognitiva. “Non mollare” diventa così sia un motto che una responsabilità civile: difendere la diversità del pensiero, la responsabilità algoritmica e il dialogo aperto come pilastri fondamentali della democrazia.